Alkaline ceramidase 2 is essential for the homeostasis of plasma sphingoid bases and their phosphates. Issue 6 (22nd January 2018) - Li, Fang; Xu, Ruijuan; Low, Benjamin E.; Lin, Chih-Li; Garcia-Barros, Monica; Schrandt, Jennifer; Mileva, Izolda; Snider, Ashley; Luo, Catherine K.; Jiang, Xian-Cheng; Li, Ming-Song; Hannun, Yusuf A.; et al.
ABSTRACT: Sphingosine‐1‐phosphate (S1P) plays important roles in cardiovascular development and immunity. S1P is abundant in plasma because erythrocytes—the major source of S1P—lack any S1P‐degrading activity; however, much remains unclear about the source of the plasma S1P precursor, sphingosine (SPH), derived mainly from the hydrolysis of ceramides by the action of ceramidases that are encoded by 5 distinct genes, acid ceramidase 1 ( ASAH1 )/ Asah1, ASAH2/Asah2, alkaline ceramidase 1 ( ACER1 )/ Acer1, ACER2/Acer2, and ACER3/Acer3, in humans/mice. Previous studies have reported that knocking out Asah1 or Asah2 failed to reduce plasma SPH and S1P levels in mice. In this study, we show that knocking out Acer1 or Acer3 also failed to reduce the blood levels of SPH or S1P in mice. In contrast, knocking out Acer2 from either whole‐body or the hematopoietic lineage markedly decreased the blood levels of SPH and S1P in mice. Of interest, knocking out Acer2 from whole‐body or the hematopoietic lineage also markedly decreased the levels of dihydrosphingosine (dhSPH) and dihydrosphingosine‐1‐phosphate (dhS1P) in blood. Taken together, these results suggest that ACER2 plays a key role in the maintenance of high plasma levels of sphingoid base‐1‐phosphates—S1P and dhS1P—by controlling the generation of sphingoid bases—SPH and dhSPH—in hematopoietic cells.—Li, F., Xu, R., Low, B. E., Lin, C.‐L., Garcia‐Barros, M., Schrandt, J., Mileva, I., Snider, A., Luo, C. K., Jiang, X.‐C., Li, M.‐S., Hannun, Y. A., Obeid, L. M., Wiles, M. V., Mao, C. Alkaline ceramidase 2 is essential for the homeostasis of plasma sphingoid bases and their phosphates. FASEB J. 32, 3058–3069 (2018). www.fasebj.org